Food systems everywhere: Improving relevance in practice - Brouwer, Inge D.; McDermott, John; Ruben, Ruerd (Elsevier, 2020)
Food systems approaches are increasingly used to better understand transitions in diets, sustainable resource use and social inclusion. Moreover, food systems frameworks are also widely used in many recent policy and foresight studies. We assess 32 highly-cited international studies, identifying and comparing differences in the frameworks used for food systems analysis, and discrepancies in the procedures to identify strategies for and performances of food system transformation. We show that the relevance of existing food systems analysis for identifying critical trade-offs and understanding relevant policies and practices for achieving synergies remains limited. While many studies are largely descriptive, some offer more practical insights into and evidence of entry points for food system transformation as well as opportunities for improving multiple food system outcomes (i.e. nutrition and health, environmental sustainability and resilience, social inclusion). We distinguish four different pathways for food system transformation and outline their analytical underpinnings, their views on multi-stakeholder governance, and how they deal with critical trade-offs between multiple food system objectives. We conclude that food systems approaches must be useful to decision makers and performance can only be improved if decision makers have a better understanding of these underlying interactions and dynamics of food systems change.